2014
DOI: 10.1002/ejic.201402420
|View full text |Cite
|
Sign up to set email alerts
|

Aminoalkyl‐1,1‐bis(phosphinic acids): Stability, Acid–Base, and Coordination Properties

Abstract: Four geminal bis(phosphinic acids), namely, aminomethylbis(H‐phosphinic acid) (H2L1) and 4‐aminobutyl‐1‐hydroxy‐1,1‐bis(R‐phosphinic acid) with R = H (H2L2), Me (H2L3) and CH2CH2COOH (H4L4), were studied. Their acid–base properties and coordination ability towards Cu2+, Ni2+ and Zn2+ ions were studied by potentiometry, UV/Vis spectroscopy and NMR spectroscopy. The amine group in H2L1 has a lower protonation constant (log Ka = 6.79) than those found for other studied bisphosphinates (log Ka = 10.75–11.05) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 53 publications
2
17
0
Order By: Relevance
“…These results are in contradiction with Kaboudin's values but in accordance with David's study. 20 Indeed, reported pka values for bis(methylphosphinic acid) are 1.95 and 3.63 corresponding to the two phosphinic acids and are in agreement with our experimental values for bis(H-phosphinic acid).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…These results are in contradiction with Kaboudin's values but in accordance with David's study. 20 Indeed, reported pka values for bis(methylphosphinic acid) are 1.95 and 3.63 corresponding to the two phosphinic acids and are in agreement with our experimental values for bis(H-phosphinic acid).…”
Section: Resultssupporting
confidence: 90%
“…To complete our study, we investigated pka values of synthesised H-HMBPi derivatives, especially as only few contradictory data are available in the literature. [19][20] Surprisingly, Kaboudin et al reported two unexpected pka values between 8.1 and 8.7 and 9.3 and 11.9 respectively for aliphatic and aromatic HMBPi. 19 These surprising results encouraged us to determine pka values of some synthesised H-HMBPi derivatives 6.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last 10 years, we have extensively studied P,P -diphenylmethylene diphosphinic acid (H 2 pcp), P,P -diphenylethylene diphosphinic acid (H 2 pc 2 p) and P,P -diphenyl-p-xylylene diphosphinic acid (H 2 pxylp) [4,5] as shown in Scheme 1. Different diphosphinic acids were also reported [6,7].…”
Section: Introductionmentioning
confidence: 98%